G421(P) Towards high negative predictive value meningitis testing in neonates. (27th April 2016) - Abelian, A; Mund, T; Pelham, H; Curran, M; Dear, PH
Abstract : Meningitis in newborn babies is difficult to rule out either clinically or microbiologically, which leads to uncertainty with regards to the initiation and the length of antimicrobial treatment, with risks of either under- or over-treating. A different diagnostic approach that will offer high negative predictive value (NPV) is needed to overcome this problem. Such an approach will shift the diagnostic emphasis on the negative result resulting in shorter antibiotic courses and earlier discharges. Methods: This novel molecular-biological assay has been developed on the basis of 16S RNA PCR technology and promises NPV of close to 100% with very small but clinically acceptable false-positive rate. The hurdles it aims to overcome are: 1) bacterial DNA contamination in reagents or introduced by handling, 2) exclusion of dead bacteria, 3) generalisability to NHS laboratories, which may lack the most advanced equipment and where time and money are limited. In this assay any free DNA is rendered non-amplifiable by photo-activated ethidium azide; intact bacteria are then lysed and their DNA amplified by single-step closed-tube nested PCR (Figure 1 ). Results: In its current format the assay has fully solved the problem of bacterial DNA contamination in reagents (Figure 2 ). The assay detected as few as one colony-forming unit of wide range of bacteria in 200 microlitres of CSF (standard neonatal specimen volume) (Figure 3 a, b), which significantly exceeds sensitivity of the reported molecular-biological assays applied to CSF and has a theoretical NPV of close to 100%. Conclusions: The assay is entering the stage of optimisation for NHS molecular-diagnostics laboratory, with a pilot case-control study and multi-centre case-control and cross-sectional studies, thereafter.